Legal approach towards water resources protection and pollution control in Malaysia - Mustafa, Maizatun (IIUM, 2004)
The significance of water resources in Malaysia is immense especially in providing water supply for domestic, agricultural and industrial consumption. However, over the years, the problem of water pollution in Malaysia is getting more serious and widespread. This situation becomes a great concern as when water is polluted; its quality deteriorates, causing problems such as health hazard and water shortage. Legal instrument has been known to be an important tool in combating the pollution of water resources. For this purposes, this paper seeks to provide an overview of the existing legal framework set up to manage and control water pollution, to highlight factors considered to be major obstacles undermining the efficacy of the law, and to provide suggestions for improvement. This paper seeks to (1) discuss the scope, jurisdiction and strategies of the present legislation with regard to inland water pollution control, (2) identify factors considered to be major impediments that undermine legal efficacy, and (3) point the way forward.